2014
DOI: 10.1108/imds-07-2014-0201
|View full text |Cite
|
Sign up to set email alerts
|

Insights into individual's online shopping continuance intention

Abstract: Purpose -The purpose of this paper is to provide insights into individual's online shopping continuance intention. The research uses the Expectation Confirmation Theory and Technology Acceptance Model as theoretical foundations to develop a model to achieve this aim. Design/methodology/approach -The research uses a cross-sectional survey research design approach. An online marketplace web site that connects buyers and sellers in Malaysia serves as the research context. Data were collected using convenience app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
72
2
11

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(104 citation statements)
references
References 72 publications
11
72
2
11
Order By: Relevance
“…Second, the study results support the finding that users' satisfaction is an important relational predictor of behavioural e-loyalty (Chung et al 2015;Ku and Chen 2014;Lin and Lekhawipat 2014;Mohamed et al 2014;Wen et al 2011;Zhao and Lu 2012). Third, the findings confirm previous results concerning the positive effect of perceived flow on the two relational variables of the proposed model (satisfaction and behavioural e-loyalty) (Hausman and Siekpe 2009;Hsu et al 2012;O'Cass and Carlson 2010).…”
Section: Academic Contributionssupporting
confidence: 88%
See 1 more Smart Citation
“…Second, the study results support the finding that users' satisfaction is an important relational predictor of behavioural e-loyalty (Chung et al 2015;Ku and Chen 2014;Lin and Lekhawipat 2014;Mohamed et al 2014;Wen et al 2011;Zhao and Lu 2012). Third, the findings confirm previous results concerning the positive effect of perceived flow on the two relational variables of the proposed model (satisfaction and behavioural e-loyalty) (Hausman and Siekpe 2009;Hsu et al 2012;O'Cass and Carlson 2010).…”
Section: Academic Contributionssupporting
confidence: 88%
“…It has been proved that individual satisfaction has a positive impact on repurchase intention (Mohamed et al 2014). Specifically, prior studies have confirmed that satisfaction is favourably related to purchase intention (Lin and Lekhawipat 2014;Pee et al 2018;Wen et al 2011;Yen and Lu 2008).…”
Section: Relational Variables In Local Food E-commercementioning
confidence: 94%
“…Convergent validity is accomplished if AVE exceeds 0.5 and all standardized factor loadings are significant while SCR surpluses 0.70 for all indicators [25,49,56,85]. Hence, construct convergent validity is verified.…”
Section: Measurement Model-confirmatory Factor Analysismentioning
confidence: 97%
“…Some services, however, may not be as convenient as in traditional market (e.g., immediate comparison among a variety of products that require tasting, smelling or sensing). Online shopping perceived usefulness could change consumers' attitudes toward purchasing [40]. Son et al [41] assert that PU has a positive effect on consumer intention to use an internet application.…”
Section: Perceived Usefulness (Pu)mentioning
confidence: 99%